Group structure and arboreal activity of Javan surili in Gunung Gede Pangrango National Park, Indonesia - AGUS PAMBUDI DHARMA; ANI MARDIASTUTI; ENTANG ISKANDAR; PUJI RIANTI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Dharma AP, Mardiastuti A, Iskandar E, Rianti P. 2026. Group structure and arboreal activity of Javan surili in Gunung Gede Pangrango National Park, Indonesia. Biodiversitas 27 (4): d270436. https://doi.org/10.13057/biodiv/d270436. The Javan surili is an endemic arboreal primate of Java whose population dynamics and behavioral ecology are strongly influenced by habitat quality and anthropogenic disturbance. This study aimed to analyze group structure, population density, and arboreal activity patterns of Javan surili in two contrasting sites, Tegallega and Sarongge Resorts, within Gunung Gede Pangrango National Park, Indonesia. Field data were collected over a 13-month period (March 2023-June 2024) using line transect surveys and scan sampling methods. A total of 10 groups comprising 40 individuals were recorded, with 25 individuals in Tegallega (6 groups) and 15 individuals in Sarongge (4 groups). Group structure showed a typical unimale polygynous system, with female-biased sex ratios of 1:1.25 in Tegallega and 1:1.13 in Sarongge, indicating stable reproductive potential. Population density was higher in Sarongge (5.99 ind/km², 2.14 groups/km², estimated 66 individuals) compared to Tegallega (3.03 ind/km², 1.33 groups/km², estimated 53 individuals), suggesting more concentrated space use and better habitat conditions. Behavioral observations revealed that feeding was the dominant activity (52.00% in Tegallega, 42.86% in Sarongge), followed by resting (21.33%, 27.14%), locomotion (14.67%, 15.71%), and social interactions (12.00%, 14.29%). All activities occurred exclusively in arboreal strata, with a strong preference for the mid-canopy layer (stratum C), which supported the highest number of plant species used for feeding and other activities. Key tree species such as Castanopsis argentea, Liquidambar excelsa, and Schima wallichii played essential roles in sustaining daily activities. These findings highlight the importance of habitat structure, particularly canopy connectivity and key food resources, in shaping Javan surili population and behavior. Differences between sites emphasize the influence of anthropogenic pressure and habitat heterogeneity, underscoring the need for targeted conservation strategies to maintain viable populations.